2009
DOI: 10.3390/molecules14051747
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, Crystal Structure and Antibacterial Activities of Transition Metal(II) Complexes of the Schiff Base 2-[(4-Methylphenylimino)methyl]-6-methoxyphenol

Abstract: Five transition metal(II) complexes, [ML2Cl2] 1~5, were synthesized from the reaction of MCl2·nH2O (M = Mn, Co, Ni, Cu, Cd) and the Schiff base ligand 2-[(4-methylphenylimino)methyl]-6-methoxyphenol (C15H15NO2, L), obtained by condensation of o-vanillin (2-hydroxy-3-methoxybenzaldehyde) with p-toluidine. They were characterized by elemental analysis, molar conductance, FT-IR spectra, thermal analysis. The structure of complex 1 was determined by single-crystal X-ray diffraction. Its crystal structure is of mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…[1][2][3][4][5][6] In recent years, metal complexes of Schiff bases have attracted considerable attention due to their remarkable biological activity, such as antifungal, antibacterial and antitumor property. [7][8][9] It has been shown that the Schiff base complexes derived from salicylaldehyde and its derivatives with primary amines, bearing the N 2 O, N 2 S, NO 2 or NSO donor sets, have interesting biological activity. [9][10][11][12] Furthermore, cobalt complexes in its varied oxidation states have become a central theme of current research because of their potentially useful properties in the realm of relevant scientific and technological fields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] In recent years, metal complexes of Schiff bases have attracted considerable attention due to their remarkable biological activity, such as antifungal, antibacterial and antitumor property. [7][8][9] It has been shown that the Schiff base complexes derived from salicylaldehyde and its derivatives with primary amines, bearing the N 2 O, N 2 S, NO 2 or NSO donor sets, have interesting biological activity. [9][10][11][12] Furthermore, cobalt complexes in its varied oxidation states have become a central theme of current research because of their potentially useful properties in the realm of relevant scientific and technological fields.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] It has been shown that the Schiff base complexes derived from salicylaldehyde and its derivatives with primary amines, bearing the N 2 O, N 2 S, NO 2 or NSO donor sets, have interesting biological activity. [9][10][11][12] Furthermore, cobalt complexes in its varied oxidation states have become a central theme of current research because of their potentially useful properties in the realm of relevant scientific and technological fields. Recently, we have reported some Schiff base complexes and their application in biological area.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In recent years, metal complexes of Schiff bases have attracted considerable attention due to their remarkable biological activity, such as antifungal, antibacterial, and antitumor. [4][5][6] It has been shown that the Schiff base complexes derived from salicylaldehyde and its derivatives with primary amines, bearing the N 2 O, N 2 S, NO 2 , or NSO donor sets, have interesting biological activity. [6][7][8] Recent research indicates that the halide-substituent groups in aromatic rings of Schiff bases or aroylhydrazones can remarkably increase the antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] It has been shown that the Schiff base complexes derived from salicylaldehyde and its derivatives with primary amines, bearing the N 2 O, N 2 S, NO 2 , or NSO donor sets, have interesting biological activity. [6][7][8] Recent research indicates that the halide-substituent groups in aromatic rings of Schiff bases or aroylhydrazones can remarkably increase the antimicrobial activity. 9 As a continuation of our work on the synthesis and structures of Schiff base complexes, 10 in the present paper, the preparation and characterization of new nickel(II) and copper(II) complexes, [Ni(BCP) 2 …”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] Furthermore, some Schiff bases are used in ion sensors and electrochemical sensors to empower detection with enhanced selectivity and sensitivity. 12,13 Due to the importance and diverse structural aspects of Schiff bases, several methods and procedures have been reported for synthesis of these compounds.…”
Section: Introductionmentioning
confidence: 99%